Geographic variation in modern contraceptive utilization among women of reproductive age in Mozambique: a multilevel analysis - Habtu Kifle Negash; Destaye Tirite Gelaw; Mihret Getnet; Hiwot Tezera Endale; Tseganesh Asefa; Fethiya Seid Hasen; Yihun Tefera Ayenew; Nebebe Demis Baykemagn; Trualem Zeleke Yehuala; Winta Tesfaye (Contraception and Reproductive Medicine)
Abstract Background Modern contraceptives are crucial for reducing maternal and child mortality, yet Mozambique’s contraceptive prevalence rate is very low, with significant regional disparities. This study investigates geographic variation in contraceptive use and the individual, community, and regional factors influencing it to guide equitable family planning interventions. Methods This study utilized data from the 2022/23 Mozambique Demographic and Health Survey, analyzing a weighted sample of 9,316 women aged 15–49. The outcome variable was modern contraceptive use, with predictors including individual factors such as age, education, wealth, and marital status, as well as community-level factors like residence and region. Data analysis was conducted using Stata 17 and ArcGIS 10.7, employing multilevel logistic regression and spatial techniques (Global Moran’s I, Getis-Ord Gi*, interpolation, and SaTScan) to identify patterns and geographic clusters of contraceptive use. Results The study found a modern contraceptive prevalence of 34.8% (95% CI: 33.84–35.78). Key factors influencing usage included age, education, wealth, and healthcare access. Women aged 25–34 were 31% more likely to use contraceptives than those aged 15–24 (AOR: 1.31, 95% CI: 1.13–1.53). Secondary education more than doubled the likelihood (AOR: 2.25, 95% CI: 1.82–2.78), and wealthier women had a 74% higher likelihood (AOR: 1.74, 95% CI: 1.39–2.17). Fieldworker visits increased usage by 38% (AOR: 1.38, 95% CI: 1.15–1.64). Regional disparities were significant, with women in Cabo Delgado 81% (AOR: 0.19 95% CI: 0.14, 0.27) less likely to use contraceptives compared to Maputo. Higher usage was concentrated in Maputo and Southeastern Gaza. Spatial analysis revealed significant regional disparities, with hotspots in Maputo and Gaza, where women are 2.52 times more likely to use contraceptives, while rural areas like Cabo Delgado lag behind. Conclusion Modern contraceptive use in Mozambique remains low, with regional disparities. Key factors influencing use include age, education, wealth, and healthcare access. Older, educated, and wealthier women are more likely to use contraception. Media exposure and proximity to healthcare facilities also play a role. Regional differences persist, with lower usage in provinces like Cabo Delgado and higher usage in urban areas like Maputo and Gaza. Targeted interventions are necessary to address these disparities.